Strategi bagi Meningkatkan Penggunaan ‘Construction Industry Payment & Adjudication Act’ (CIPAA) dalam Industri Pembinaan - Wan Zuki, Wan Nor Nabila Nasuha; Sarpin, Norliana; Masrom, Md. Asrul Nasid (Research in Management of Technology and Business, 2020)
The payment’s problem is an issue that has long shackled industry players in the construction sector. A special act to deal with the contents related to payment was gazette by the Ministry of Works on 22nd June 2012 and implemented on 15th April 2014 known as Construction Industry Payment and Adjudication Act (CIPAA). Due to the fact that CIPAA is still new in Malaysia, there are many problems and challenges for contractors to apply CIPAA if they have problems related to payment. Therefore, this study was conducted to identify the main challenges faced by contractors while using CIPAA and to proposed strategies to increase the use of CIPAA in the construction industry. The methodology uses in this study is a quantitative method by using a questionnaire instrument with the population of G7 contractor respondents in Selangor. A total of 50 respondents, representing 36% of the study sample, provided feedback on the questionnaire. The data collected were analyzed using Microsoft Office Excel in percentage form. This study has identified several key challenges faced by contractors while using CIPAA, namely CIPAA prioritizes financial problems between main contractors and clients, contractors prefer other methods than CIPAA, parties involved have to bear the cost during the adjudication period, and confusion throughout the adjudication period. Meanwhile, some strategies to increase the use of CIPAA is to provide a special website related to CIPAA, get support from all parties, especially contractors’ associations, and the time period for CIPAA evaluation needs to be increased. Through this study, it is expected to provide useful information related to CIPAA to the contractors involved in payment issues in the construction sector.